2022
DOI: 10.1111/bjhp.12608
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between subjective social status and health: Evidence from a Chinese cohort study

Abstract: Using nationally representative longitudinal data from 2010 to 2018 in China, this study systematically investigates the relationship between Subjective Social Status (SSS) and health (physical health and mental health) in the Chinese adult population. Methods: By applying between-within model, we disentangle the relationship between health outcomes and:(1) between-individual differences in SSS and (2) withinindividual variations of SSS across time. In addition, to explore SSS mobility and trajectory, we furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Our research focused on subjective SES, perceived mobility of SES, and mobility expectation of SES and these are represented by the self-rated current SES. Besides subjective SES, we also took perceived social mobility of SES and perceived social mobility expectation of SES as the independent variables because social mobility could be used to assess the fairness of the society and is closely related to health [ 50 ]. Though the SES variables did not significantly predict trust in the regression models, subjective SES and SES upward mobility expectation were significantly related to trust in the healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research focused on subjective SES, perceived mobility of SES, and mobility expectation of SES and these are represented by the self-rated current SES. Besides subjective SES, we also took perceived social mobility of SES and perceived social mobility expectation of SES as the independent variables because social mobility could be used to assess the fairness of the society and is closely related to health [ 50 ]. Though the SES variables did not significantly predict trust in the regression models, subjective SES and SES upward mobility expectation were significantly related to trust in the healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Invidious upward social comparisons would lead to perceived relative deprivation, which is negatively associated with self-rated health in both urban and rural older people [ 52 ]. Current studies based on a large-scale survey, such as China Family Panel Studies, also showed that subjective social status was correlated with health, personal relative deprivation had negative effects on the health of the Chinese population, and individuals with high expected mobility were found to have significantly better health [ 50 ]. Our research further verified that low subjective SES and low mobility expectation of SES led to low trust in the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 2010 CFPS, a multistage probability distribution was used to stratify the sample. As a result, five provinces/regions (Gansu, Guangdong, Henan, Liaoning, and Shanghai) were selected for initial over-sampling (1600 households in each, or an aggregate of 8000) to obtain regional comparisons, and another 8000 households were selected by weighting from the remaining provinces/regions to make the overall CFPS sample nationally representative 11 12. The response rates each year were more than 80% both at the household level and individual level.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, Chinese society has long been characterized by health inequalities between urban and rural residents ( 1 – 3 ), especially in mental health ( 4 , 5 ). A meta-analysis showed that the prevalence of depressive symptoms was nearly 10% higher in rural areas than in urban areas ( 6 ).…”
Section: Introductionmentioning
confidence: 99%